2013
DOI: 10.1371/journal.pone.0081596
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence for Multiple Strains of Canine Norovirus in the UK Dog Population

Abstract: Noroviruses are associated with intestinal disease in humans, cows, pigs, mice, and, more recently, dogs. In 2007, the first canine norovirus (CNV) was identified and characterized in Italy. Subsequent studies have identified CNV in stools of dogs from Portugal, Greece, and the United States. To investigate the prevalence of CNV in the UK dog population, 228 canine stool samples were screened for CNV by qPCR, and 396 serum samples were screened for anti-CNV antibodies. qPCR of RNA extracted from canine stool s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 30 publications
3
30
3
Order By: Relevance
“…Although a comparison of the seroprevalences between countries was not possible because the number of samples tested from several of the countries was limited, the detection of IgG antibodies in dogs from 12 of the 14 countries demonstrates that GVI.2 CNVs are widespread in dogs throughout Europe. The percentage of samples positive for GVI CNV antibodies in our study (36%) was higher than the 4.8% reported for GIV CNV antibodies in dogs from Italy (11) and fell within the range (38.1% to 60.1%) reported for the dog population of the United Kingdom (10). However, the 36% seropositivity found in this study must be interpreted with caution, since it may be an overestimate due to antibody cross-reactivity.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Although a comparison of the seroprevalences between countries was not possible because the number of samples tested from several of the countries was limited, the detection of IgG antibodies in dogs from 12 of the 14 countries demonstrates that GVI.2 CNVs are widespread in dogs throughout Europe. The percentage of samples positive for GVI CNV antibodies in our study (36%) was higher than the 4.8% reported for GIV CNV antibodies in dogs from Italy (11) and fell within the range (38.1% to 60.1%) reported for the dog population of the United Kingdom (10). However, the 36% seropositivity found in this study must be interpreted with caution, since it may be an overestimate due to antibody cross-reactivity.…”
contrasting
confidence: 52%
“…These data might indicate either a certain level of antibody cross-reactivity with GII.4 VLPs or multiple reactivities to canine GVI.2 and human norovirus in the same dog sera. Cross-reactivity to human norovirus and other canine norovirus strains is not expected to be present, as was demonstrated in recent studies (10,12). Conversely, the presence of antibodies to human GII.4 norovirus in dogs is plausible, since human GII.4 norovirus was recently detected in fecal samples from pet dogs that had been in direct contact with symptomatic persons who were confirmed to be infected with GII.4 norovirus (13).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Evidence for CNV infection has since been identified in Europe (1820) and the Far East (21). CNV is believed to cause gastroenteritis in the canine host, though the virus has also been isolated from healthy dogs (19, 22).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis of the complete amino acid sequence of VP1 showed that these strains are distantly related to other NoV genogroups and were proposed as the seventh NoV genogroup (GVII) [5]. Furthermore, it was reported that there was a marked rise in seroprevalence of the novel GVII NoV over the last decade in dogs in the United Kingdom, suggesting that this genogroup is becoming increasingly common, at least in the UK [31]. However, there are no additional studies reporting GVII NoV strains in other countries.…”
mentioning
confidence: 99%